a). 2x - 5 = x + 7
b). 3x - 7 = 41
c). 2x + 8 = x + 25 + 8
d). 3x + 23 = 2x + 59
e) x + 12 = 17
1. 2x - 4 = x + 9
g) 5x - 10 = 4x - 12
Respuestas
Respuesta dada por:
1
Respuesta:
no entiendo
Explicación paso a paso:
no me deas nada
Respuesta dada por:
0
Respuesta:
a) x=12
b) x=16
c) x=25
d) x=36
e) x=5
f) x=13
g) x=-2
Explicación paso a paso:
a) 2x-5=x+7
2x-x=7+5
x=12
b) 3x-7=41
3x=41+7
3x=48
x=16
c) 2x+8=x+25+8
2x-x=25+8-8
x=25
d) 3x+23=2x+59
3x-2x=59-23
x=36
e) x+12=17
x=17-12
x=5
f) 2x-4=x+9
2x-x=9+4
x=13
g) 5x-10=4x-12
5x-4x=-12+10
x=-2
Preguntas similares
hace 4 años
hace 4 años
hace 4 años
hace 7 años
hace 8 años